Comparative analysis of the prototype and the simulator of a new load balancing algorithm for heterogeneous computing environments. (8th August 2005) - De Mello, R.F.; Trevelin, L.C.; De Paiva, M.S. V.; Yang, Laurence Tianruo
The availability of low cost hardware has increased the development of distributed systems. The allocation of resources in these systems may be optimised through the use of a load balancing algorithm. The load balancing algorithms are responsible for the homogeneous distribution of the occupation in the environment, with the aim of obtaining gains on the final performance. This paper presents and analyses a new load balancing algorithm that is based on a logical computer tree hierarchy. The analysis is made using results obtained by a simulator and a prototype of this algorithm. The algorithm simulations show a significant performance gain by lowering the response times and the number of messages that pass through the communication system to perform the load balancing operations. After good results were obtained by the simulations, a prototype was built and validated such results.